2018
DOI: 10.7441/joc.2018.01.02
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Manufacturing Industry on the Economic Cycle of European Union Countries

Abstract: The manufacturing industry is a key sector in many national economies and is involved in creating sustainable economic growth. At the same time, it is a sector sensitive to internal and external impacts that result in fluctuations in the economic cycle, copying its development or even outstripping the development of economic cycles. The main objective of this contribution was to identify the relationship between manufacturing and GDP, which represents the economic cycle in European Union countries. The time se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 26 publications
3
44
0
2
Order By: Relevance
“…One of the major challenges comforting SME management currently is technological and managerial innovation. They are an essential determinant of economic development not only from the point of view of the microsphere but also in the evaluation of macroeconomic development and forecasting of economic cycles of countries (Behun et al 2018). In the literature, it was also concluded that SMEs could be managed adequately by paying critical attention to those dual keys mentioned above and making sure it is properly introduced to the organisational system of SMEs (Žufan et Currently, the use of information and communication technology cannot be overlooked regarding the role been played by this key factor (Ion & Andreea, 2008;Zadorozhnyi et al, 2018).…”
Section: Literature Review 21 Management Of Smesmentioning
confidence: 99%
“…One of the major challenges comforting SME management currently is technological and managerial innovation. They are an essential determinant of economic development not only from the point of view of the microsphere but also in the evaluation of macroeconomic development and forecasting of economic cycles of countries (Behun et al 2018). In the literature, it was also concluded that SMEs could be managed adequately by paying critical attention to those dual keys mentioned above and making sure it is properly introduced to the organisational system of SMEs (Žufan et Currently, the use of information and communication technology cannot be overlooked regarding the role been played by this key factor (Ion & Andreea, 2008;Zadorozhnyi et al, 2018).…”
Section: Literature Review 21 Management Of Smesmentioning
confidence: 99%
“…Innovative development is determined by a company's size as well as its economic sector. As many studies prove (Gavurova et al, 2017a;Behun et al 2018;Civelek et al, 2016;, medium and large companies were focused on operational effectiveness and cost savings for a longer period of time, while a certain space for smaller companies had been created in order to respond to the environmental changes by innovations. Many research studies also prove that the more organizationally-challenged company, the lower is its adaptability to innovative changes (Hudec & Šebová, 2012;Gavurova et al, 2017c;Belás & Sopkova, 2016;Rahman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As the first three industrial revolutions demonstrated that technology has a major impact on the labor market and the business environment, we expect the current phenomenon of accelerated digitization of the economy, known as the Fourth Industrial Revolution, to have positive effects on competitiveness by increasing productivity, but also a notable impact on the labor market, through the creation/disappearance of jobs and the emergence of completely new occupations [22,23]. Creating new business models, based on increasing connectivity, reducing communication barriers and eliminating distances, amplifies development factors, changes the way of adding value, leading to increased productivity [24].…”
Section: Literature Reviewmentioning
confidence: 99%